Posted by **Anonymous** on Thursday, February 11, 2010 at 8:50pm.

Transform to a Cartesian Equation:

a. x = sin t

y = cos t

b. x = t^(1/3) -1

y = t^2 - t

---

This is what I have for B so far:

y = t(t-1)

t = (x+1)^3

y = (x+1)^3[(x+1)^3-1]

= (x^3 + 3x^2 + 3x + 1)[x^3+3x^2+3x]

...???

and IDK about A.

Help?

Thank you so much!

## Answer this Question

## Related Questions

- Math - Solve this equation algebraically: (1-sin x)/cos x = cos x/(1+sin x) --- ...
- TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...
- tigonometry - expres the following as sums and differences of sines or cosines ...
- calculus - PLEASE HELP! Transform polar equation to an equation in Cartesian (...
- calculus - PLEASE HELP! Transform polar equation to an equation in Cartesian (...
- Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...
- Math - Calculus - The identity below is significant because it relates 3 ...
- algebra - Can someone please help me do this problem? That would be great! ...
- trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...
- math - Eliminate the parameter (What does that mean?) and write a rectangular ...